Combustion and emission characteristics of premixed biogas mixtures: An experimental study. (19th March 2022) - Sivri, Ilker; Yilmaz, Harun; Cam, Omer; Yilmaz, Ilker
Abstract: In this study, effects of fuel composition, swirl number and hydrogen addition on combustion and emission characteristics of various biogas mixtures were experimentally investigated. To this end, a laboratory scale combustor and a swirl stabilized premixed burner were designed and manufactured. Later on, this combusting apparatus was equipped with flow, control, safety and measurement tools, hence entire test system was constituted. Combustion and emission characteristics of tested biogas mixtures were determined by measuring temperature and species (CO2, CO, O2 and NO) distributions throughout the combustion chamber. Additionally, flame structures of tested biogas mixtures were evaluated by examining flame luminosity, visible flame length and flame thickness from instantaneous flame images. Results of this study showed that both radial and axial temperature distribution variations of tested biogas mixtures differently alter with hydrogen addition based on the gas composition. Although flame temperature increases with swirl number at burner outlet, it presents a non-monotonous dependence on swirl number outside the flame region because of the modified flow characteristics. This is also the case for emissions of CO2 . Highlights: Premixed combustion characteristics of various biogas mixtures were investigated. Gas composition, swirl number and hydrogen addition effects were examined. Hydrogen addition differently altered temperature distribution based on the gas composition. Flame temperature presented a non-monotonous dependence on swirl number.